Hubungan Keaktifan dalam Organisasi dengan Disiplin Belajar Himpunan Mahasiswa Jurusan di FIP UNP - Adrian Antoni; Syahril Syahril; Sulastri Sulastri; Hadiyanto Hadiyanto (Journal of Educational Administration and Leadership, 2021)
The study was conducted in order to obtain information about the relationship between activity in the organization and the learning discipline of the student association of FIP UNP as seen from their activity in the organization (variable X) and learning discipline (variable Y). The student population in HMJ FIP is 445 people with a sample of 86 people taken using the Slovin formula. The instrument in this study used a Likert scale questionnaire through validity and reliability tests. This data uses the product moment correlation with the Rh value of 0.220> Rt 0.215 and Th 2.07> Tt 2.00. The result of his research is that there is a relationship between activeness in the organization and the learning discipline of the student association of FIP UNP`